THE PANDEMIC, THE WAR AND THE CLIMATE CRISIS - Mihai GOȚIU (International Journal of Social and Educational Innovation, 2023)
The years 2021 and 2022 saw a warning from communication and disinformation experts about the emergence of an ad hoc alliance with long term effects between supporters of conspiracy theories related to the pandemic and climate change deniers. The war in Ukraine has made things only worse. In August 2021 the first section of the 6th IPCC report (”Code Red for Humanity”) had a relatively good visibility. However, the launch of the full report, in April 2022, has gone largely unnoticed. In addition to shifts in attention, the war in Ukraine has generated two opposite communication directions: an ambitious one, calling for the urgent reduction of overall dependence on fossil fuels (not just from Russia), and a conservative one, justifying postponement of decarbonisation plans. The latter has already been used in Romania to adopt laws with a significant environmental impact. Last but not least, there is a convergence both nationally and globally (at the levels of human and financial resources, communications channels, messages) of conservative (justifying the attack of Russia in Ukraine through the prism of the defence of traditional values), conspiratorial (related to the pandemic and the promoters of the progressive discourse) and denialist discourses (in relation to climate change).